Plasma Eicosanoid Profile in Plasmodium vivax Malaria: Clinical Analysis and Impacts of Self-Medication - Abreu-Filho, Péricles Gama; Tarragô, Andrea Monteiro; Costa, Allyson Guimarães; Monteiro, Wuelton Marcelo; Meielles, Alyne Fávero Galvão; Costa, Thainá Cristina Cardoso; Silva, Jéssica Santos; Zambuzi, Fabiana Albani; Gardinassi, Luiz Gustavo; Moraes, Luiz Alberto Beraldo; Lacerda, Marcus Vinícius Guimarães; Sorgi, Carlos Arterio; et al. (Frontiers in Immunology, 2019)
The participation of cytokines and chemokines in Plasmodium vivax malaria (Pv-malaria) activates the immune response and thus causes the production of several inflammatory mediators. This process is already well established, but little is known about eicosanoids in malaria physiopathology, especially in regards to inflammation and immunity. Malaria is an acute febrile syndrome similar to any other less important infectious disease and people may self-medicate with any anti-inflammatory drugs in order to cease the recurrent symptoms of the disease. Based on this information, the study describes the eicosanoid profile and its possible influence on the production of cytokines and chemokines in P. vivax infections. In addition, we investigated the influence of self-medication with anti-inflammatory drugs in this immune profile. Twenty-three patients were included in the study, with or without self-medication by anti-inflammatory drugs prior to diagnosis. A total 12 individuals were selected for the control group. Eicosanoid profiles were quantified by HPLC-MS/MS, and cytokines and chemokines by flow cytometry and ELISA. The Pv-malaria infection significantly reduces the production of several lipid mediators, and its action is increased by self-medication. We observed that the eicosanoids we found derive from the lipoxygenase and cyclooxygenase pathways, and present positive and negative correlations with chemokines and cytokines in the follow-up of patients. Our data suggest that self-medication may interfere in the immunological characteristics in P. vivax infection and may modify the follow-up of the disease.